Silence phenomenon after teacher’s post-question wait-time in Vietnamese EFL classroom = hiện tượng học sinh giữ im lặng sau khi giáo viên kết thúc thời gian chờ sau mỗi câu hỏi tại lớp học tiếng Anh ở Việt Nam - Đặng, Nguyệt Thu (2020)
Silence phenomenon in education is a research area of educational psychology, which has been taken into investigation for decades. Silence phenomenon has a strong connection with classroom management because it affects both teacher and students in class. Some scholars claim that students’ silence can take positive effects on students as it allows them to spend time thinking. Others argue that this phenomenon is negative because it limits cooperation and interaction between teacher and students, which impacts on teaching and learning process. Silence phenomenon, in general, has its own merits in education; however, the reasons behind are unknown. This is the motivation for the researcher to conduct this study with a view to (1) unveiling reasons beyond students’ silence, (2) finding out the common types of teacher’s questions and the allocation of wait-time for each of them together with (3) figuring out teacher’s strategies to deal with silent students. This study adopted mixed methods research which is about the combination of qualitative and quantitative methods. In particularly, the author made use of three different data collection instruments namely questionnaire, observation and semi-structured interview. The results from data analysis showed that personal problems were students’ most frequent reasons for not responding actively to teacher’s questions. Also, understanding question type was the most common category that teacher used in class. Lastly, teacher strongly prefered rewarding system as a method of encouraging silent students to participate in class.